Self-Orientalist Representations of Turkish Classical Music in the Republican Era: Orientalism and Orientalism in Reverse - Ayas, Onur Gunes (VWB-VERLAG WISSENSCHAFT & BILDUNG, 2024)
The critique of Orientalism in music studies has tended to focus on European Orientalism rather than the Orientalism of Orientals. The purpose of this study is to explore how Turkish classical music (TCM) was represented in self-Orientalist discourses of R epublican Turkey as part of competing strategies to define Turkish musical identity. These dis-courses not only perpetuate and reproduce the essentialist conceptions of European Orientalism, but also reformulate them in a different setting, sometimes contrasting their own interpretation with that of the Europeans. Whether they otherize or embrace the non-Western elements in Turkish music, most of these competing discourses share the same system of representation based on an essentialized and de-historicized conceptualization of culture. This also applies to some of the counter-dis-courses which emerged as a reaction to the symbolic violence imposed by Westernizing music policies in Republican Turkey. Despite their criticism of European Orientalism, they merely reverse its essentialist ontology to favor TCM. Using a wide range of sources, including the writings of influential Turkish thinkers, officials, and musicologists as well as periodicals and newspapers, this study aims to show the common conceptual background in the negative and positive representations of TCM from the 1920s to the present
Keywords: OTTOMAN; Music